SPEAKERâS VISION AND ATTITUDES THROUGH DEICTIC EXPRESSIONS - Sofwan, Ahmad; Bouk, Edmundus (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2014)
This study addresses how deictic expressions of person, place and time account for vision and attitudes of a speaker in speeches on certain issues. In this qualitative study, the data consisted of four speeches delivered by Xanana Gusmao of Timor Leste. The result of the study shows that the speaker used various types of deixis, including person, place, and time deixis. Person deixis was used to introduce Timorese people, whereas more time deixis referring to present time was used to focus his attention on the present situation and did not want to turn back to the past experience with full of political and social conflicts. The speakerâs vision is reflected in the use of the first person plural âweâ more than the first person singular âIâ or âmeâ. This indicates that the speaker represents himself as an âinsertiveâ leader. He is also a sort of leader with more future vision, indicated by the use of more time deixis referring to the present and future time than those of past time, so he wanted to bring his people and nation to face the future to develop the nation and to build better relationship with its neighbouring states.